An approach to financial information analysis by the Brazilian Federal Police - Filho, Renato Kettner; Macedo, Douglas D. J. de (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: One of the tasks performed by the Federal Police is the verification and cross-referencing of data contained in Financial Intelligence Reports (FIRs) produced and forwarded by the Financial Activities Control Council (COAF) - an activity in which, among the police involved, the absence of a standard system of execution.OBJECTIVES: The present work aims to present a study on the form currently in use within the scope of the Federal Police Station regarding the analysis of FIRs from the COAF, then presenting a methodology suggestion, aiming to speed up the process. Regarding open sources, the objective is to carry out a survey of possible complementary repositories not yet used and to expose ways of implementing queries.METHODS: Pointing out the workflow currently used (displaying it in graphic form) as well as identifying the data sources consulted (open sources and closed sources) during the process,CONCLUSION: understanding how the FIR analysis system is currently carried out, identifying possible aspects for improvement, and suggesting a methodology to be used, indicating for this the use of files in a specific format (.CSV), exclusion of queries in similar repositories (System “A”) and, mainly, the automation of part of the procedure (with the use of the RIBOT prototype software).
Keywords: COAF; Financial Intelligence Reports; FIRs; Polícia Federal; Python; Workflows; Financial Crimes